KARAKTERISTIK PENDERITA DIABETES MELLITUS TIPE 2 DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN TAHUN 2016 - Swanry Yanti Nainggolan; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Diabetes Mellitus (DM) is a group of metabolic disease. According to International Diabetes Federation (2015), global prevalence of DM in adults aged 20-79 years reached 8,8%. Based on data from Riskesdas 2013, the prevalence of diabetes was 2,1% in Indonesia. The purpose of this study is to know the characteristics of patients of type 2 DM with complications who were hospitalized in RSUP Haji Adam Malik Medan in 2016. This research is descriptive with case series design. The population is the people of type 2 DM with complications who are hospitalized. Sample of 150 people, taken with simple random sampling. The data was collected by using secondary data and analyzed with Chi-Square and Kruskal Wallis. The result showed the proportion of patiens with complications of type 2 DM was highest in the age group >40 years (94,0%), female (51,3%), Bataknese (64,0%), Moslem (48,6%), Senior High School (52,0%), housewife (34,6%), married (77,3%), live outside Medan (62,0%), diabetic feet (38,0%), chronic complication (78,0%), insulin (54,7%), BPJS (91,3%), average length of stay 10 days, becoming outpatient (68,7%). The statictical test resulted, there was no difference in the proportion of age by sex (p=0,741), age based on category of complication (p=0,319), sex based on category of complication (p=0,173), category of complication based on medicine (p=0,908), avarage length of stay based on category of complication (p=0,051), there was difference category of complication based on condition by going home (p=0,003). It suggest to the hospital and medicine personnel can be an educator to prevent diabetes mellitus complication to increase patient of diabetes mellitus chronic. Patients of type 2 diabetes mellitus with complications diciplint to do the recommended diet and for age group ≤40 years to always keep a balanced life style and diet. Keywords: Chracteristics, Type 2 Diabetes Mellitus with Complications